Cefiderocol resistance genomics in sequential chronic Pseudomonas aeruginosa isolates from cystic fibrosis patients. (April 2023) - López-Causapé, Carla; Maruri-Aransolo, Ainhize; Gomis-Font, María A.; Penev, Iván; Castillo, María García; Mulet, Xavier; de Dios Caballero, Juan; Campo, Rosa del; Cantón, Rafael; Oliver, Antonio
Abstract: Objective: To evaluate the activity of cefiderocol against sequential P. aeruginosa isolates from chronically-infected cystic fibrosis patients as well as to investigate the potential mechanisms involved in resistance through whole genome sequencing. Methods: Three sequential P. aeruginosa isolates from each of 50 chronically-colonized cystic fibrosis patients were studied. MICs for novel and classical antipseudomonal agents were determined by broth microdilution and whole genome sequences ( n = 150) were obtained to investigate the presence of mutations within a set of chromosomal genes involved in P. aeruginosa antibiotic resistance ( n = 40) and iron uptake ( n = 120). Results: Cefiderocol showed the lowest MIC50/90 values and its susceptibility rate was comparable to other novel antipseudomonal agents. Clinical resistance was documented in 9 isolates from 6 patients. Resistance genes associated with a statistically significant increase in cefiderocol MICs included ampC, pmrAB, galU, fusA1 and those coding the penicillin-binding proteins PBP2 and PBP3. Likewise, mutations within several genes participating in different iron-uptake systems were found to be significantly associated with resistance, including genes participating in the pyochelin and pyoverdin biosynthesis and several tonB -dependent receptors. Mutator and small colony variants isolates were also associated with increased cefiderocol MICs. Discussion: Cefiderocol resistance is modulated by a complex mutational resistome, potentially conferring cross-resistance to novel beta-lactam beta-lactamase combinations, as well as an extended list of mutated iron-uptake genes. Monitoring the acquisition of mutations in all these genes will be helpful to guide treatments and mitigate the emergence and spread of resistance to this novel antibiotic.